Simulations numeriques d'electrophorese de particules spheriques et de courts batons dans des systemes microfluidiques - Dube, Antoine (University of Ottawa (Canada), 2010)
This thesis consists of two articles that have been submitted to peer reviewed scientific journals. In addition, three introductory chapters precede the articles: one presenting the theory behind the work described in the articles, a second one presenting the methods used for the simulations and a third one summarising results published in literature by different research groups. The first article presents the results of the optimization of the pulse sequence during the electrophoresis of spherical particles in a gel and the presentation of two new types of pulse sequences: the correlated random telegraph signal and the dichotomous signal. Our results show that the optimal ratio of pulse durations in each direction t+/t - should be around 5, compared to a value of 2 or 3 generally used in experiments. In the second article, we explore the dynamics of rod-like DNA fragments in a 2D version of the system of Han et al. [1]. Our simulations present results that contradicts the statement made by Laachi and coworkers [2] why longer chains elude faster at high field: the "torque-assisted escape", where torque turns the DNA chains in a favourable conformation. Our results show that the torque caused by the electric field is in fact in the opposite direction to the movement near the constriction zone. Following those two articles, another chapter presents some supplementary results. The exact calculation method used for the optimization of the pulse sequences was also used to simulate a rotating field in a modified version of the system of asymmetric traps presented by Torres & Slater [3]. Our results show that separation of spheres of different sizes can be made along different directions, offering the possibility of continuous separation. In the second part of this chapter, we present the results of the separation of spherical particles in the system of Han et al. We present a new idea, the pulsed signal, and a new mode of operation with this signal.
Keywords: Physics, Condensed Matter.; Physics, Fluid and Plasma.